2015
DOI: 10.1111/hiv.12277
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir and atazanavir in pregnancy: comparable infant outcomes, virological efficacies and preterm delivery rates

Abstract: Both ART regimens were well tolerated and successful in preventing MTCT. No significant differences in tolerability or in pregnancy or infant outcomes were observed, which supports the provision of a choice of PI in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In addition, data describing other risk factors for preterm birth or SGA were not available in our data set. Perry et al recently showed no differences in preterm birth or birth weight in infants exposed to maternal LPV/r versus ATV; this study did not report infant laboratory outcomes [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, data describing other risk factors for preterm birth or SGA were not available in our data set. Perry et al recently showed no differences in preterm birth or birth weight in infants exposed to maternal LPV/r versus ATV; this study did not report infant laboratory outcomes [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…A retrospective study from the UK reported a PTD rate of 10% in 100 women taking atazanavir/r in pregnancy, of whom 67% had conceived on their regimen . The same group found no difference in PTD rates in a retrospective study comparing lopinavir/r and atazanavir/r as the third agent in cART . The latest publication from the NSHPC suggests that atazanavir/r has a lower PTD rate than lopinavir/r, particularly in women with a CD4 count <350 cells/mm 3 and compared to darunavir/r in women initiating cART in pregnancy .…”
Section: Current Issues In the Use Of Art In Pregnancy And Pregnanmentioning
confidence: 99%
“…Remdesivir is currently being evaluated in a randomized clinical trial for the treatment of patients with Ebola virus disease (NCT03719586). The combination of lopinavir and ritonavir is an FDA approved antiviral for the treatment of human immunodeficiency virus (HIV) infections (Croxtall and Perry, 2010;Perry et al, 2016). Previous studies on the antiviral activity of lopinavir against MERS-CoV are conflicting with one study reporting micromolar EC 50 values in a human hepatoma cell line (Huh 7) yet another reported that lopinavir had no activity in a non-human primate kidney cell line (Vero) de Wilde et al, 2014).…”
Section: Remdesivir Provides Superior Therapeutic Efficacy To Lopinavmentioning
confidence: 99%